0117 Nonmalignant Disease Mortality among Styrene, Fibreglass, and Wood Dust Exposed Workers in the Reinforced Plastic Boatbuilding Industry. (23rd June 2014) - Meyers, Alysha; Bertke, Steve; Ruder, Avima
Abstract : Objectives: To further evaluate the association of styrene, fibreglass, and wood dust exposure with non-malignant diseases, we extended follow-up through 2008 for 5203 workers exposed to styrene, fibreglass, and wood dust between 1959 and 1978 at two boat building plants. Method: We used a person-years analysis program, LTAS.NET to compute standardised mortality ratios (SMRs) using Washington State and U.S. rates, standardised rate ratios (SRRs), and 95% confidence intervals. SMRs were stratified by exposure category (low or high) and duration of employment category (≤ 1 year, 1+ years). Results: Overall, 1206 nonmalignant deaths occurred (WA SMR 1.14, CI 1.08–1.21), with excess mortality for chronic obstructive pulmonary disease (COPD) overall (n = 112, WA SMR 1.61, CI 1.32–1.93), and among 2063 workers highly exposed to styrene and fibreglass (n = 39, WA SMR 2.37, CI 1.69–3.25). Results were similar using U.S. mortality rates. Workers employed for less than one year had statistically significant increased mortality from several lifestyle-related outcomes (alcoholism, ischaemic heart disease, cirrhosis, accidental poisoning and homicide). Conclusions: The excess COPD mortality in this cohort is difficult to interpret. Recent reports associate styrene/fibreglass reinforced plastic manufacturing with another respiratory disease - bronchiolitis obliterans. Based on a review of COPD death certificates, bronchiolitis obliterans does not appear to be a contributing factor for excess COPD mortality. The COPD excess in this study points to a need for an in-depth investigation of respiratory disease and occupational styrene exposure. Short term worker results are consistent with other occupational cohort studies.